Erythema nodosum arising during everolimus therapy for tuberous sclerosis complex. Issue 4 (16th May 2018) - Galligan, Eloise R.; Fix, Lindsey; Levin, Laura E.; Imundo, Lisa; Yamashiro, Darrell J.; Garzon, Maria C.
Abstract: Indications for everolimus and other drugs within the mammalian target of rapamycin inhibitor class have recently expanded to include tuberous sclerosis complex. Everolimus is generally well tolerated, but it is important for physicians to identify and manage associated cutaneous adverse effects. We report the first case of a child developing erythema nodosum while undergoing everolimus therapy.